Run-time manipulation of programs in a statically-typed language - Greiner, Sašo (Informatica (Ljubljana), 2009)
This article is an extended abstract of a doctoral dissertation on metaprogramming and programming language design. A metaprogramming model is studied and implemented in a statically-typed pure object- oriented programming language Zero. The object model of language is based on closures which enables metaprogramming model to achieve a high degree of dynamic manipulation, normally only found in dynamically-typed languages. Metaprogramming in Zero is based on safely-typed structural and behavioural reflection.
Keywords: programski jeziki; metaprogramiranje